Assessing the quality and readability of online content on shock wave therapy for erectile dysfunction. (14th October 2022) - Reddy, Raghuram V.; Golan, Roei; Loloi, Justin; Diaz, Parris; Saltzman, Russell G.; Watane, Arjun; Ramasamy, Ranjith
Abstract: Patients are becoming increasingly reliant on online platforms for obtaining health information. Previous research has shown that the quality of information available on the internet regarding novel medical therapies is generally poor and frequently misleading. Shock wave therapy represents a novel restorative therapy for erectile dysfunction (ED) that has recently gained attention. We hypothesised that online sources regarding shock wave therapy for ED would be fraught with misleading claims and unreliable health information. Our objective was to evaluate the quality and readability of online medical information on shock wave therapy as a treatment for ED. Websites were generated using a Google search of 'shock wave therapy for erectile dysfunction' with location filters disabled. Readability was analysed using the Readable software (Readable.com, Horsham, United Kingdom). Quality was assessed independently by three reviewers using the DISCERN tool. Articles were subdivided into those from private clinic websites and those from universities or news media websites. Statistical analysis was conducted using the Student's t test. Nine articles that resulted from the Google search had mean readability scores as follows: Flesch–Kincaid grade level (10.8), Gunning–Fog Index (13.67), Coleman–Liau Index (12.74), Simple Measure of Gobbledygook (SMOG) Index (13.33), FORCAST Grade Level (11.33), and Automated Readability Index (11.08). The mean Flesch Reading Ease score was 46.4. The articles had a mean DISCERN score of 3.1, suggesting 'moderate quality' content. Articles from universities ( n = 2) or news sources ( n = 3) had significantly higher DISCERN scores than articles from private medical practices ( n = 4). There was no difference in readability scores between the groups. Articles from private clinics are just as readable as those from universities or news media, but they are significantly more biased and misleading. The current online material relating to shock wave therapy for ED may not adequately inform patients in their medical decisions making, thereby necessitating closer collaboration between the sources disseminating information and urologists.